Tinjauan Kembali Penelitian Grounded Teori : Sejarah Asal Mula dan Teknik Analisis Riset Kebijakan - Nukyanto, Damainsa Prahesti; Zuhrotul, Devy Riesta (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
Grounded Theory is an inductive research method that generates theories systematically by using qualitative and/or quantitative data generated from observations, interviews, or written sources such as documents, or some combination obtained through rigorous methods. Currently, the grounded theory method has been applied in various research fields, including policy research. Although grounded theory has been used for more than 50 years in publications, papers and textbooks on research methodology, many researchers still find it difficult to apply the grounded theory approach in their research. The purpose of this short paper is to explain an overview of the historical origins of grounded theory, the development of grounded theory, when is the right time to use grounded theory, and how the steps of data analysis techniques using grounded theory methods in policy research where hypotheses are built from data and from data grounded theory is generated.